Pengaruh Struktur Modal, Ukuran Perusahaan dan Profitabilitas terhadap Nilai Perusahaan Pada Persahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Ayuni Saputri; Andri Widianto (Indonesian Accounting Research Journal, 2021)
Abstract: Firm value is an investor’s perception of the value of the company’s success which is closely related to stock prices. This study was aimed to determine the effect simultaneously and partially of the variables of structure capital, company size, profitability and company value. The data collection techniques used were documentation and literature study. The data analysis technique was quantitative using Quantitative Descriptive Statistical Analysis, Classical Assumption Test (Normality Test, Heteroscedasticity Test, Multicollinearity Test, Autocorrelation Test), Multiple Linear Regression Analysis, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The results of hypothesis testing using the t test (partial test) showed that capital structure, firm size and profitability have a significant effect on firm value. And the result of the F test (simultaneous test) showed that capital structure, firm size and profitability have a significant effect on firm value. Keywords: Capital Structure (DER), Company Size (SIZE), Profitability (ROE), Companies Value (PBV)